As oficinas de teatro no processo de ensino e aprendizagem e na formação dos professores de língua inglesa: um estudo q - Coêlho, Margarete Afonso Borges (2010)
The main goal of this study is to investigate and analyze the cognition of pre-service teachers and also of the teacher researcher of this study about the use and possible contributions of drama workshop to the teaching and learning process and to the education of English language teachers. I understand that by analyzing the points of view and opinions of those involved, I can get a better understanding of the teaching and learning process and of the education of pre-service teachers. In a qualitative approach, four different tools were used: focus groups, "Q" Distribution (Q Methodology), reflective sessions and questionnaire. The focus group was used as a secondary instrument to collect data for further development of the Q sample, which is the primary tool in the use of the Q methodology research approach. This Q sample was used in the Q Distribution of pre-service teachers of the third term of a Letras course of a private institution of a higher education Institute in Alto Paranaíba. These participants distributed the sample items throughout a scale ranging from "more likely my point of view" (+5) to "least likely my point of view" (-5) and the results were initially submitted to a factor analysis via a statistical package called PQmethod. From the triangulation of data obtained through the above mentioned instruments and through the qualitative and interpretive analysis, the groups that emerged from the factor analysis were defined, characterized and interpreted by the teacher researcher. The participants share points of view in the perspective of Language Learners (group A), Language Teachers (groups B and C) and Critics (group D). The teacher researcher was also investigated and revealed her cognitions in line with the Language Learners and with the Language Teachers, which may indicate a perspective tending towards the dichotomy: linguistic development and professional education in Letras Course.